Perancangan Interior Children Daycare Kiddy Planets Di Surabaya - Harsono, Ameilia (Intra, 2013)
Child is an individual who developing into adults. Within each level of age, the childâs development is also increasing rapidly. Therefore, it is necessary to know the childâs understanding deeper. In modern times, there are many organizations or agencies that put full concentration in children. Due to globalization, the parents have their own busy and in the end they did not have much time for children, so that childrem get less attention. Development of a child is an important part of childrenâs education. Developing childrenâs creativity at this age.